A treasure chest for teachers and children too : themes to foster multiple intelligences - Wood, Beth.; Jorgensen, Glenda (Dalby, Qld : Heads Together, 1994)
The Units of Work included in this texts provide teachers with a multitude of practical ideas for curriculum activities; activities which will allow chidren to respond in their own way and varying levels of complexity.
Keywords: Education; Cognition; Activity programs in education; Teaching; Thought and thinking -- Study and teaching; Intellect; Cognitive styles